Regulation on Genetically Modified Animals: Proposed and Its Possible Application in Indonesia - Bess Tiesnamurti; Sri Muharsini; M I Shiddieqy (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2021)
The government is responsible for fulfil the needs of safe, healthy and halal food for all its people in a sustainable manner. The world population will increase from 7 to 9 billion people in 2050. While the availability of land may not increase in the future, it may even not be used for agriculture. Scientists are trying to overcome this problem by creating technologies that can increase livestock productivity, one of which is through a genetically modified process. Genetically modified animals are animals that have been genetically modified for many  purposes including yields and disease resistance. Although genetically modified animals are at the last stage of research and the possibility to entering Indonesia remains small, but government should prepare a regulation related to it. European countries and USA have regulations to control genetically modified animals. Malaysia also has applied a similar regulation since 2007. Currently, Indonesia has formed an authority that oversees the genetically modified product, namely Biosafety Commission (Komisi Keamanan Hayati) on genetically modified products. However, this commission only supervises genetically modified organism in food and feed. This paper is aimed to propose the regulation for genetically modified animal that may be entering Indonesia and or be researched by Indonesian scientists.